MENGUAK STRATIFIKASI SOSIAL KIAI, HAJI, DAN ULAMA - Sukarno (Al'Adalah, 2006)
Human being is equal before Allah, except because of one spiety (taqwa). But in social life, human being is different and stratified into several degree. Social stratification happens in society because everyone has different ability in accessing dimension, privilege, prestige, and status. This article aims to give some explanation about the phenomena of hajji, Moslem scholar (Ulama') and Kyai from the economic, power and status perspectives. When these social phenomena in Moslem society are analyzed with social stratification theory, they will explain the character of social change in our society in general. The conclusion suggests that (1) Haji is an achieved status because of existence of economic wealthy, and the Moslem society perceive someone who own the hajji title as an ordinary citizen, because hajji is a religious obligation and the fifth pillar of Islam: (2) Kyai is achieved stains, social stratification transformation, and vertical social mobility. This title is given to someone who has expertise in religious knowledge and become the exemplar of the society. Kyai is an informal and non-formal leader who reaches respectable .status and power in society, and economically become the wealthy class; and (3) Title ulama (Moslem scholar) is an achieved status because of religious piety and intellectuality. He obtain honored place in society, and also has formal and non-formal power, and pertains to an higher economic class.